Transmedia narratives to raise awareness about the mining pollution of rivers in Ecuador: A review for the environmental awareness - Largo Loayza, Jorge (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The human being is one of the main actors of environmental pollution; however, the lack of awareness has brought with it different factors that directly affect the earth. The purpose of this research is to analyze the social impact of transmedia narratives in the face of mining contamination of rivers in southern Ecuador. Among the results, in Ecuador, there have been more than 1,128 cases of diseases caused by mining contamination in rivers, but thanks to transmedia journalism it has been possible to influence man's responsibility with the environment Abstract in English.